Decoding halophilic biofilm development across salinity gradients in hypersaline environments - ILHAM MISBAKUDIN AL ZAMZAMI; DEFRI YONA; ABD RAHEM FAQIH; ANDI KURNIAWAN (Society for Indonesian Biodiversity, 2025)
Abstract. Al Zamzami IM, Yona D, Faqih AR, Kurniawan A. 2025. Decoding halophilic biofilm development across salinity gradients in hypersaline environments. Biodiversitas 26: 2773-2785. Halophilic microorganisms possess distinctive adaptations that enable survival and biofilm formation under extreme salinity, exhibiting considerable promise for biotechnological applications. However, halophilic biofilms' structural and biochemical properties across varying salinity gradients remain insufficiently characterized. The present study investigates the biofilm formation on High-Density Polyethylene (HDPE) substrates in NaCl concentrations ranging from 2% to 40% over 21 days. A multidisciplinary approach was employed to characterize biofilm development and microbial responses. This approach included metagenomics, Confocal Laser Scanning Microscopy (CLSM), Fourier-Transform Infrared Spectroscopy (FTIR), and water quality analyses. The results demonstrated that optimal biofilm formation occurred at 20% NaCl, exhibiting peak microbial abundance, biovolume, protein content, and metabolic activity, accompanied by increased acid production, decreased pH, and reduced dissolved oxygen. Conversely, 40% NaCl elicited a substantial response characterized by severe osmotic stress, a marked deterioration in cell viability and biofilm integrity, and a notable elevation in turbidity consequent to cellular damage. Biofilms at 2% NaCl were stable but exhibited reduced metabolic activity and simpler structures. These results highlight the adaptive capacity of halophilic biofilms, especially at moderate salinities, providing essential insights into their ecological roles and applications in saline wastewater treatment and sustainable environmental management.